Internalisasi Nilai-Nilai Keislaman Melalui Kegiatan Pesantren Ramadhan (Studi Kasus Di MAN Bondowoso, Jawa Timur) - Maula, Atika Rofiqatul; Fathani, Sahrizal (Balai Diklat Keagamaan Surabaya, 2022)
Pesantren Ramadan activities are a series of activities in the form of deepening Islamic values, both in terms of worship and in behavior. One of the institutions that carry out this activity is MAN Bondowoso, where the activity is carried out offline. The purpose of this article is to find out the concept applied by MAN Bondowoso in carrying out the Pesantren Ramadan (PESROM), as well as the values instilled in it. This research is qualitative research, that is, data sources obtained through documents and interviews online. The results of this study showed that the material delivered when PESROM was about the fikih of worship and the realization of Islamic values in the form of discipline, spirit of worship, noble character and religious moderation.